Optimization of the Synthesis of Oleyl Oleate from Olive-based Fatty Acid by Response Surface Methodology - W. M. K. Anwar W. M. Z.; Mat Radzi, S.; Mohd Amin, N.; Mohd Rehan, M. (Institut Kimia Malaysia, 2024)
Indexed by Scopus